1991
DOI: 10.1111/j.1365-313x.1991.00083.x
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the auxin signal at the plasma membrane of tobacco mesophyll protoplasts

Abstract: SummaryAuxin-induced variations of transmembrane potential difference have been shown to be a useful tool for analyzing hormone sensitivity in tobacco protoplasts.Using this technique, we demonstrated that protoplasts derived from wild-type, an auxin-resistant mutant and Agrobacterium-rhizogenes transformed plants differed widely in the sensitivity of their electrical response to naphthalene acetic acid. We have used different antibodies, raised to auxin binding proteins (ABP) from maize coleoptiles, or to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(65 citation statements)
references
References 28 publications
4
61
0
Order By: Relevance
“…Protoplasts from tobacco plants transfonned by Agrobacterium rhizogenes T-DNA, especially by the single rolB gene, exhibit an increased sensitivity of their electrical response to auxin (Maurel et al, 1991b). This finding is in agreement with a number of reports in which an increased sensitivity to auxin was described for excised organs, isolated protoplasts, or membrane vesicles from various plant materials containing the whole pRi T-DNA or some of its subfragments (Shen et al, 1988(Shen et al, , 1990; Spano et al, 1988;Barbier-Brygoo et al, 1991;Vansuyt et al, 1992). These findings suggested that morphogenetic effects of pRi T-DNA transformation might involve changes in hormone responsiveness and/or hormone content.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Protoplasts from tobacco plants transfonned by Agrobacterium rhizogenes T-DNA, especially by the single rolB gene, exhibit an increased sensitivity of their electrical response to auxin (Maurel et al, 1991b). This finding is in agreement with a number of reports in which an increased sensitivity to auxin was described for excised organs, isolated protoplasts, or membrane vesicles from various plant materials containing the whole pRi T-DNA or some of its subfragments (Shen et al, 1988(Shen et al, , 1990; Spano et al, 1988;Barbier-Brygoo et al, 1991;Vansuyt et al, 1992). These findings suggested that morphogenetic effects of pRi T-DNA transformation might involve changes in hormone responsiveness and/or hormone content.…”
supporting
confidence: 82%
“…The E, of protoplasts was measured under the microscope by the microelectrode te$nique as describeli previously (Ephritikhine et al, 1987;Barbier-Brygoo et a]., 1991). For each NAA concentration tested, 15 to 20 individual measurements were performed at room temperature on an aliquot of the protoplast stock solution diluted to 5 X 104 protoplasts/ mL in To medium with the appropriate NAA dose, and a mean E, value was calculated.…”
Section: Electrical Response Of Mesophyll Protoplasts To Auxinmentioning
confidence: 99%
“…In the same year, it was also proven that ABP1 indeed binds auxin (Jones and Venis, 1989), a result that was later corroborated by the crystal structure determination of ABP1 cocrystallized with auxin (Woo et al 2002). ABP1 antibodies and peptides generated in these biochemical studies were increasingly used for physiological studies in heterologous systems, showing auxin induction of cellular processes such as membrane hyperpolarization (Barbier-Brygoo et al, 1991;Venis et al, 1992), K + fluxes (Thiel et al, 1993), or cell expansion, as evidenced by protoplast swelling assays (Steffens et al, 2001). The importance and function of ABP1 for the plant as a whole remained unclear because attempts to modulate ABP1 protein amounts (particularly, its' downregulation) proved difficult in planta.…”
Section: Timeline Of Abp1 Researchmentioning
confidence: 85%
“…Auxin is one of the major stimuli affecting these mechanisms but it is essential to keep in mind that cell expansion is also under the control of many other stimuli, such as blue light and most of the other phytohormones. Auxin-dependent cell expansion follows a dose-response curve in which high concentrations are inhibitory (Barbier-Brygoo et al 1991;Evans et al 1994). The apparent response-maxima varies according to both the plant and the organ with shoots and roots showing differences in sensitivity of several orders of magnitude.…”
Section: Auxin On Division and Expansionmentioning
confidence: 99%